2017
DOI: 10.3201/eid2305.161873
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blood Donor Screening Data to Estimate Zika Virus Incidence, Puerto Rico, April–August 2016

Abstract: Puerto Rico has been heavily impacted by Zika virus, a mosquitoborne flavivirus that emerged in the Americas during 2015. Although most persons with Zika virus show no symptoms, the virus can cause neurologic and other complications, including fetal microcephaly. Local Zika virus transmission in Puerto Rico has been reported since December 2015. To prevent transfusion-associated transmission, local blood collection ceased in March 2016 but resumed in April 2016 after Zika virus screening of blood donations bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Third, we determined the best fit parameter sets for the epidemiological variables using a least-squares approach. For Puerto Rico, we computed the human-to-mosquito transmission rate that produced a 23.5% attack rate, as observed during the Puerto Rico Chikungunya outbreak (27), and computed the mosquito seasonality parameters which best fit the observed Zika epidemic trajectory over the period January 17, 2016 through July 21, 2017 (28,29) (Figure S2). When not otherwise specified, we used the Puerto Rico best-fit attack rate as our base case.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we determined the best fit parameter sets for the epidemiological variables using a least-squares approach. For Puerto Rico, we computed the human-to-mosquito transmission rate that produced a 23.5% attack rate, as observed during the Puerto Rico Chikungunya outbreak (27), and computed the mosquito seasonality parameters which best fit the observed Zika epidemic trajectory over the period January 17, 2016 through July 21, 2017 (28,29) (Figure S2). When not otherwise specified, we used the Puerto Rico best-fit attack rate as our base case.…”
Section: Methodsmentioning
confidence: 99%
“…13 ZIKV RNA persists significantly longer in whole blood than in plasma. 18,19 In June of 2016, as a result of the ZIKV epidemic affecting the Americas, our transplant center started screening all local deceased donors for ZIKV with ZIKV IGM and IGG and plasma and urine ZIKV PCR. 16 An investigation in Florida suggested that urine PCR might be the most sensitive test to diagnosis acute infection in symptomatic patients due to higher and more prolonged detection rates of ZIKV.…”
Section: Introductionmentioning
confidence: 99%
“…ZIKV screening for blood donors has been reported. 18,19 In June of 2016, as a result of the ZIKV epidemic affecting the Americas, our transplant center started screening all local deceased donors for ZIKV with ZIKV IGM and IGG and plasma and urine ZIKV PCR. The aim of this study was to evaluate the rates of positive ZIKV testing and risk factors for ZIKV among deceased donors in our transplant center located in an area of autochthonous ZIKV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Its occasionally severe pathogenicity in combination with the detection of asymptomatic but viremic blood donors in French Polynesia, Martinique, Puerto Rico and the US and three probable cases of ZIKV transfusion‐transmission in Brazil have made ZIKV a concern for blood safety. Guidelines and countermeasures have been published by the European Centre for Disease Prevention and Control (ECDC), the WHO, and the American Food and Drug Administration (FDA) to reduce the blood safety risk originating from ZIKV .…”
mentioning
confidence: 99%
“…6,7 However, more severe complications such as Guillain-Barré syndrome in adults 8,9 and microcephaly and other congenital malformations in the developing fetus and newborns [10][11][12][13][14] have been associated with ZIKV infection and led to the declaration of ZIKV as a Public Health Emergency of International Concern by the World Health Organization (WHO) in 2016. 15 Its occasionally severe pathogenicity in combination with the detection of asymptomatic but viremic blood donors in French Polynesia, Martinique, Puerto Rico and the US [16][17][18][19][20][21][22] and three probable cases of ZIKV transfusion-transmission in Brazil 23,24 have made ZIKV a concern for blood safety. Guidelines and countermeasures have been published by the European Centre for Disease Prevention and Control (ECDC), the WHO, and the American Food and Drug Administration (FDA) to reduce the blood safety risk originating from ZIKV.…”
mentioning
confidence: 99%